The Ecological Scarcity Method for the European Union: A Volkswagen Research Initiative: Environmental Assessments - Stephan Ahbe (AutoUni - Schriftenreihe, 2017)
This report transfers the Ecological Scarcity Method (ESM) to the EU and its 28 member states. It provides a powerful tool for unbiased environmental assessments in enterprises and surveys the current impacts and the targets published by environmental authorities, specifically the European Environment Agency. ESM assesses environmental impacts of manufacturing sites and production processes. Developed in 1990 in Switzerland, ESM has already gained regulatory status in proving entitlements for tax exemptions. The method assesses all important impacts in air, water, energy consumption, waste generation and freshwater consumption and also supports en vironmental investment decisions.